Driving manoeuvre during lane maintenance in older adults: Associations with neuropsychological scores. (February 2018) - Sun, Qian (Chayn); Xia, Jianhong (Cecilia); Foster, Jonathan; Falkmer, Torbjörn; Lee, Hoe
Highlights: Advanced GNSS tracking vehicle trajectory was used to assess older drivers' lane maintenance. Lower visual selective & divided attention in older drivers associated with higher MLP & SDLP. MLP was positively correlated to spatial visualisation, executive function and motor speed. Selective attention was found to be the best predictor of MLP in lane maintenance. Combined neuropsychological tests classified 80.4% drivers as good & poor lane maintenance. Abstract: Older drivers experience difficulties in lane maintenance under challenging driving sections due to age-related cognitive declines, yet there is little comprehensive evidence on associations between cognitive functions and the lane maintenance in this population. In this study, fifty older drivers completed an on-road driving assessment and a battery of standard neuropsychological tests. Mean Lane Position (MLP), Standard Deviation of Lane Position (SDLP) and manoeuvre time calculated from precise vehicle movement trajectories were used as the lane maintenance parameters. The GNSS tracking vehicle movement presents comprehensive and reliable vehicle position data, which is more sensitive for detecting subtle variations of lane maintenance in older drivers. Statistical analysis results showed that lower visual attention (selective and divided attention) was associated with higher MLP and SDLP; MLP was also correlated to spatial abilities, executive function, and motor speed; manoeuvre time was negatively correlated with drivers' risk-taking personality (all p < .01). Selective attention was found to be the best predictor of MLP in lane maintenance. A combined eight variables from three neuropsychological tests, UFOV 2 and 3, BD and BJLO, D-KEFS TMT 1, 2, 3, and 4, correctly classified 80.4% of participants with good versus low-performing lane maintenance.